Characterizing Barium Titanate Piezoelectric Material Using the Finite Element Method - Butt, Zubair; Rahman, Shafiq Ur; Pasha, Riffat Asim; Mehmood, Shahid; Abbas, Saqlain; Elahi, Hassan (Transactions on electrical and electronic materials, 2017)
The aim of the current research was to develop and present an effective methodology for simulating and analyzing the electrical and structural properties of piezoelectric material. The finite element method has been used to make precise numerical models when dielectric, piezoelectric and mechanical properties are known. The static and dynamic responses of circular ring-shaped barium titanate piezoelectric material have been investigated using the commercially available finite element software ABAQUS/CAE. To gain insight into the crystal morphology and to evaluate the purity of the material, a microscopic study was conducted using a scanning electron microscope and energy dispersive x-ray analysis. It is found that the maximum electrical potential of 6.43 V is obtained at a resonance frequency of 35 Hz by increasing the vibrating load. The results were then compared with the experimentally predicted data and the results agreed with each other.